PEMBELAJARAN INTERAKTIF BAHASA INGGRIS BAGI SISWA KELAS 2 SEKOLAH DASAR (STUDI KASUS MI NURUL FALAH CIATER) - Nining Suryani; Ridho Wijayanto (Paradigma, 2014)
The process of teaching and learning in education can not be separated from the methods and tools used for appropriate methods and tools can make an impact in both the teaching and learning process. For example, the process of learning the method of discussion, this method is quite effective to help students speak up and argue. One is the lcd that can be used as a medium of learning. In addition to the use of the lcd, there are many media that can be used, such as the use of multimedia instructional media in the form of an interactive animation. MI Nurul Falah Ciater is one of the schools that provide English language learning with the conventional method . Where teachers and students still interact face to face in teaching and learning English in particular subjects. Delivery of a material that is less attractive to make them feel bored making the lack of interest in students in learning English. In addition the use of tools materials book for giving students the English language makes less understood because the posts with different pronounsition. So, we need other instructional tools, one of which is an interactive learning tools. This instructional tools can be made using methods based multimedia development cycle Mc Leod . In this interactive lesson contains material related to adjectives, clothes, body, address, meals, time, activities, position and support the use of evaluation and application . Based on the results of the questionnaire that 74 % of students can use this application with easy , and can help in pronunciation and writing, and more interested in learning English, and can help students to make the process of learning and more creative in the learning process.